Analisis Cukur, Waxing, dan Krim Pada Hair Removal Ketiak Paling Efektif dan Ekonomis bagi Mahasiswi PKK: Penelitian - Mia Hafizah Tumangger; Taofan Ali Achmadi; Wahyu Widaningsih; Faza Zahra Hendriyana; Dewinta Putri Sahbrina; Nabila Avrilian Farohmah; Maulidya Eka Putri; Evi Veronika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the comparison of three underarm hair removal methods shaving, waxing, and depilatory cream in terms of effectiveness, comfort, irritation risk, and cost efficiency among students of the Family Welfare Education (PKK) Study Program. The research employed a qualitative approach with a case study design involving 25 students who regularly perform hair removal. Data were collected through structured surveys and in-depth interviews, then analyzed inductively to identify key themes. The findings reveal that shaving is preferred for its practicality and low cost, waxing is the most effective and long-lasting method, while depilatory creams are considered the most comfortable and suitable for sensitive skin. The study concludes that no single method is universally superior; the optimal choice depends on balancing practicality, effectiveness, comfort, and individual skin conditions.